Penyuluhan KB dan Sosialisasi Gerakan Konseling Kontrasepsi Menggunakan Aplikasi “KlikKB” Sebagai Upaya Penurunan Unmet Need KB di Kota Pekanbaru: Penyuluhan KB dan Sosialisasi Gerakan Konseling Kontrasepsi Menggunakan Aplikasi “KlikKB” Sebagai Upaya Penurunan Unmet Need KB di Kota Pekanbaru - Ismainar, Hetty; Marlina, Hastuti; Rahmalisa, Uci (Jurnal Pengabdian Kesehatan Komunitas, 2023)
In Indonesia the unmet need for family planning in 2017 reached 10.6%, Riau 25.6% (2021) while the national target (5%). The public's low level of knowledge or understanding about family planning and the reluctance of PUS to visit health services are the main problems. In order to simplify the family planning counseling process, in 2022 the government created the "KlikKB" application as a family planning communication medium for people throughout Indonesia, but utilization is not evenly distributed. The aims to increase public knowledge and understanding about family planning through outreach and introduction of the Contraception Counseling Movement using the KlikKB application. The activity was carried out at RT 02/RW 08, West Sidomulyo, Pekanbaru. The counseling method is health education, questions and answers and filling out questionnaires about family planning knowledge. Participants are given pre and post tests while practicing the KlikKB application through observation with a checklist sheet. The number of participants was 35 people. The average pre-test value for family planning knowledge is 45%. The post test score increased with an average of 72.3%. The majority of the KlikKB application practice assessments were in the "unable to" category (46.2%), the "with help" category (38%) and the "proficient" category was only 15.8%. Providing education about family planning can increase mothers' knowledge. Meanwhile, to socialize the contraceptive counseling movement with the KlikKB Application, continuous assistance and collaboration with the local community health center is needed